Pengaruh Citra Merek dan Harga Terhadap Minat Beli di Koi Thé Mall Central Park Jakarta - RB, Linda Desafitri; Ingkadijaya, Rahmat; Angelina, Sheila Canistha (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2021)
This study aims to determine brand image and price on buying interest at Koi Thé Mall Central Park Jakarta. The research method used in this research is multiple linear regression with quantitative qualitative research. The population in this study are consumers of Koi Thé Mall Central Park Jakarta. The sample in this study amounted to 100 respondents. The sampling technique used is purposive sampling. The results of the study partially brand image and price have a significant effect on buying interest at Koi Thé Mall Central Park Jakarta. Brand image is a seller's promise to consistently provide certain benefits and services to buyers. Prices are adjusted to the benefits received by consumers, where consumers want the price paid in accordance with the benefits received. It is recommended that Koi Thé improve its brand image by expanding its sales market, so that consumers can find KOI Thé products in the area where consumers live. Koi Thé must be able to regulate and determine the price of the product properly in accordance with the quality and quantity of the product so as not to lose competition with other bubble drink brands. Keywords: Brand Image, Price, Buying Interest